2005
DOI: 10.1007/s10809-005-0130-x
|View full text |Cite
|
Sign up to set email alerts
|

Voltamperometry of Aromatic Nitro Compounds Using a Multisensor System of Electrodes Modified with Poly(Arylene Phthalide Ketones)

Abstract: Electrodes modified with poly(arylene phthalide ketones) were developed for the voltammetric determination of isomers of aromatic nitro compounds. A polynomial algorithm for processing analytical signals from a sensor array was tested in the analysis of ternary mixtures. It is shown that the sensor array offers promise for analyzing multicomponent mixtures in the case when analytical signals overlap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…19 In recent years, dye molecules have been widely used as mediators to study the electrocatalytic reduc-tion of nitro compounds. 20,21 In general, the derivatives of dyes covalently bound to an aromatic ring could decrease their proton-donor ability, resulting in improved catalytic activity. 22 Polymerization of dyes could form a crosslinked oligomer, which leads to the enhancement of its electrocatalytic ability.…”
Section: Introductionmentioning
confidence: 99%
“…19 In recent years, dye molecules have been widely used as mediators to study the electrocatalytic reduc-tion of nitro compounds. 20,21 In general, the derivatives of dyes covalently bound to an aromatic ring could decrease their proton-donor ability, resulting in improved catalytic activity. 22 Polymerization of dyes could form a crosslinked oligomer, which leads to the enhancement of its electrocatalytic ability.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches demonstrated that electropolymerization is a very convenient way to immobilize polymers on electrode surface and the thickness, permeation and charge transport characteristics of the polymeric films can be controlled by the potential and current applied. Dye molecules have been widely used as mediators to study the electrochemical reduction of nitro compounds [9,10], including methylene blue [11,12], methylene green [13] and brilliant cresyl blue [14]. In general, the derivatives of dyes formed via bonding a dye molecule to an aromatic ring covalently could decrease their proton-donor ability and improve their adsorptive activity [15].…”
Section: Introductionmentioning
confidence: 99%